STUDY OF EFFECT OF DRYING AGENT COMPONENT ON CLEANING EFFICIENCY - ROZMETOV, RAKHMATJON; Kuliyev , Toxir; Tuychiev , Timur (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract: It was determined that the change in the speed and temperature of the air supplied to drying significantly affects the change in the cleaning efficiency of the cotton cleaning equipment. Cotton with an initial moisture content of 9.5% and impurities of 5.4% at air temperatures of 120 and 140 °C, 2.5; 4.0; After drying at speeds of 5.5 and 7.0 m/sec, the cleaning efficiency of the equipment is 29.3; 32.5; 35.2; 40.1% and 32.1%; 34.6; 38.4; showed an increase to 41.5%. The cleaning efficiency of the equipment is 35.1 when the cotton is dried and cleaned after the temperature rises to 160 and 180 °C without changing the air speed; 37.6; 44.2; 46.8 and 38.2; 41.2; 46.4; It showed an increase to 52.5%. Cotton with an initial moisture content of 11.3% and impurities of 6.2% at air temperatures of 120 and 140 °C, 2.5; 4.0; After drying at the speed of 5.5 and 7.0 m/sec, the cleaning efficiency of the equipment is 27.4; 30.3; 33.1; 37.9 % and 34.8; 38.2; 41.5; showed an increase to 43.1%. The cleaning efficiency of the equipment is 36.6 when the cotton is dried and cleaned in the equipment when its temperature rises to 160 and 180 °C without changing the air speed; 39.6; 45.3; 51.4 % and 40.2; 42.8; It showed an increase to 53.6 and 61.7%.